Audit quality and audit size: Evidence from auditor mergers in China. Issue 3 (23rd April 2020) - Zhan, Jun; Her, Young‐Won; Chen, Keji
Abstract: Focusing on the surge of mergers among Chinese local accounting firms around the year 2000, this study examines the impacts of auditor mergers on audit quality, and documents increased earnings quality for non‐Big 5 clients during the postmerger period. The study also brings up the question for further investigation, whether the Big 5 auditors provide significant higher quality audits than the non‐Big auditors do in China, a far less litigious audit market environment, during the period of 1999–2002. We find limited differences in terms of audit quality between the Big 5 and non‐Big 5 auditors. We do not find significant differences in reported discretionary accruals and probability of reporting losses between Big 5 clients and non‐Big 5 clients. Only with the earnings conservatism proxy, clients with Big 5 recognize bad news more quickly than non‐Big 5 clients. Furthermore, findings of this study suggest the Big 5 audits do not contribute to the accruals quality differences in China, implying legal enforcement and litigation risks have greater propensity to drive auditor incentives.